Política na raça: trajetória política e perfis sociais de políticos pretos, pardos e brancos na câmara dos deputados - Santos, João Victor Penha dos (2023)
"What is the face of Brazil's National Congress?" This dissertation was developed with the aim of answering this question, but above all, to echo the typical profile of elected representatives in the country. Using race as the primary category of discussion, this dissertation is anchored in recent data provided by the Superior Electoral Court (TSE) during the 55th and 56th legislatures (2015-2019; 2019-2023), which also categorize race/color as an element of candidate information. Based on the literature on political recruitment, political elites, and political professionalization, and using empirical data on federal deputies, the research compared white, black, and brown deputies in both legislatures in terms of their social profiles and political trajectories. As expected, it was found that black deputies were underrepresented compared to white deputies; however, counterintuitively, there were few differences between white and black deputies in terms of their social profiles and political trajectories. In terms of social profile, both tend to have completed higher education, the majority are men, around 53 years old, and with a significant percentage having graduated in law. In terms of political profile, both showed trajectories with experience in various positions and in the different levels of the Brazilian federative system, showing that they are professionalized when they arrive at the Chamber of Deputies. No significant differences were identified between the two legislatures.